If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + 3 = 84 Reorder the terms: 3 + 9m = 84 Solving 3 + 9m = 84 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 9m = 84 + -3 Combine like terms: 3 + -3 = 0 0 + 9m = 84 + -3 9m = 84 + -3 Combine like terms: 84 + -3 = 81 9m = 81 Divide each side by '9'. m = 9 Simplifying m = 9
| 5x^3(2x^4+4x^2+7x-2)= | | 29X+7=5(X+7) | | 904,320/x=113,040 | | x/10=-22/5 | | -(r-5-4p)= | | 8r+2r-5r--19r+4r=16 | | x + 3y = 10 | | 0.75a=14.25 | | -(0.6)(-0.3x)(1.5)(-1)=b | | (7x^3-15x^2-9)-(3x^3+5x+15)= | | 8b^5+20b^3+2b^2+12b=0 | | 2(x-5)=3-2(7-x) | | 20=s-25 | | 7x+1=2-x | | 2m-m+4m=15 | | 350=140r | | (6x^2+19x+2)+(-4x^2+10x-11)= | | -7+13b+(-6b)-b= | | y-2=7/3(x-6) | | 30+41= | | -5(1-5x)+5(-8x-2)=-4+-8x | | F(x)=5x^2+11x-12 | | -14k--19k-8k=-18 | | 4x^2-14x=2(2x^2-7x) | | 12x+5=17x-10 | | (x^2-4x+4)(x^2+9)= | | y-x^2= | | 4.5x-2=2.5x+8 | | s/19=150 | | 8b^5+20b^3+48H^4x^2=0 | | 14xd=154 | | 14k-19k-8k=18 |